P‐145: Submillisecond Grayscale Response Time of a Uniform Lying Helix Liquid Crystal. Issue 1 (2nd June 2017) - Gou, Fangwang; Lee, Yun-Han; Tan, Guanjun; Hu, Minggang; Lan, Yi-Fen; Tsai, Cheng-Yeh; Wu, Shin-Tson
Abstract : A reasonably good alignment of a uniform lying helix (ULH) liquid crystal is achieved and its gray‐to‐gray (GTG) response time investigated. The averaged GTG rise time is 0.35 ms and fall time is 0.53 ms. Such a fast response time helps suppress image blurs and color breakup for field‐sequential color displays.